Electronic structure and magnetic properties of 3d-4f double perovskite material - Kundu S.; Pal A.; Chauhan A.; Patro K.; Anand K.; Rana S.; Sathe V.G.; Joshi A.G.; Pal P.; Sethupathi K.; Nanda B.R.K.; Khuntia P. (My University, 2025)
Double-perovskite-based magnets wherein frustration and competition between emergent degrees of freedom are at play can lead to novel electronic and magnetic phenomena. In this paper, we report the electronic structure and magnetic properties of an ordered double perovskite material, Ho2CoMnO6. In the double perovskites with general class A2BB′O6 (A = rare-earth ions; B, B′ = transition metal ions), the octahedral B and B′ sites have a distinct crystallographic site. The Rietveld refinement of x-ray diffraction data reveals that Ho2CoMnO6 crystallizes in the monoclinic P21/n space group. X-ray photoelectron spectroscopy confirms the charge state of cations present in this material. The temperature dependence of magnetization and specific heat exhibits a long-range ferromagnetic ordering at Tc∼76 K owing to superexchange interaction between Co2+ and Mn4+ moments. Furthermore, the magnetization isotherm at 5 K shows a hysteresis curve that confirms the ferromagnetic behavior of this double perovskite. We observed a reentrant glassy state in the intermediate-temperature regime, which is attributed to inherent antisite disorder and competing interactions. A large magnetocaloric effect has been observed much below the ferromagnetic transition temperature. Temperature-dependent Raman spectroscopy studies support the presence of spin-phonon coupling and short-range order above Tc in this double perovskite. The stabilization of magnetic ordering and charge states is further analyzed through electronic structure calculations. The latter also infer the compound to be a narrow-band-gap insulator with the gap arising between the lower and upper Hubbard Co d subbands. Our results demonstrate that antisite disorder and complex 3d-4f exchange interactions in the spin lattice account for the observed electronic and magnetic properties in this promising double perovskite material. © 2022 American Physical Society.